PENGARUH SALES PROMOTION, STORE ATMOSPHERE DAN KEPRIBADIAN KONSUMEN TERHADAP IMPULSE BUYING PADA KONSUMEN ALFAMART DI KECAMATAN SUMBAWA - Adinda Nurul Auliya; hartini (Publika Citra Media, 2026)
This study aims to examine the influence of sales promotion, store atmosphere, and consumer personality on impulse buying in Alfamart consumers in Sumbawa District. The background of the research is based on the growth of modern retail stores and the need to understand the factors that influence consumer purchasing decisions. The method used is a quantitative approach with an associative approach, using primary data in the form of a questionnaire distributed to 100 respondents selected by a purposive sampling technique. Data analysis used multiple linear regression. The results showed that sales promotion, store atmosphere, and consumer personality significantly influenced impulse buying. This study concludes that these three variables have an important role in encouraging consumer impulse buying behavior at Alfamart.